2021
DOI: 10.3389/fmicb.2021.698436
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hypoxia Adaption Causes Distinct Effects on Growth and Bioactive Compounds Synthesis in an Entomopathogenic Fungus Cordyceps militaris

Abstract: Cordyceps militaris is an entomopathogenic fungus producing a variety of bioactive compounds. To meet the huge demand for medicinal and edible products, industrialized fermentation of mycelia and cultivation of stromata have been widely developed in China. The content of bioactive metabolites of C. militaris, such as cordycepin, is higher when cultivated on silkworm pupae than on rice or in broth. However, compared with other cultivation methods, C. militaris grows more slowly and accumulates less biomass. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recently, the natural cordycepin content was biologically increased to more than twofold in the entomopathogenic medicinal fungus C. militaris using newly designed techniques of optimized cultivation and fermentation, which significantly enhanced the biosynthesis of this precious bioactive metabolite . Cordycepin could also be easily synthesized from many readily available simple starting materials, such as d -glucose, d -xylose, and adenosine, using different chemical synthetic routes. , Cordycepin molecule is specifically a nucleosidic adenosine molecule that lacks only one hydroxyl group at the 3′ position of the five-membered ring of its ribose moiety (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the natural cordycepin content was biologically increased to more than twofold in the entomopathogenic medicinal fungus C. militaris using newly designed techniques of optimized cultivation and fermentation, which significantly enhanced the biosynthesis of this precious bioactive metabolite . Cordycepin could also be easily synthesized from many readily available simple starting materials, such as d -glucose, d -xylose, and adenosine, using different chemical synthetic routes. , Cordycepin molecule is specifically a nucleosidic adenosine molecule that lacks only one hydroxyl group at the 3′ position of the five-membered ring of its ribose moiety (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that improving the hypoxic adaptability of the fungus contributes to the synthesis of the active substance. For example, our team overexpressed the predicted bHLH transcription factors of sterol regulatory element binding proteins (SREBPs) in vivo, which increased the cordycepin content more than two-fold, providing a scientific basis for optimizing the cultivation and fermentation gas supply strategy [227]. Xia et al [223] identified four highly homologous protein-coding genes (Cns1, Cns2, Cns3, and Cns4) in C. militaris.…”
Section: Cordycepinmentioning
confidence: 99%